The effect of positioning on preterm infants' sleep–wake states and stress behaviours during exposure to environmental stressors. (December 2014) - Peng, Niang-Huei; Chen, Li-Li; Li, Tsai-Chung; Smith, Marlaine; Chang, Yu-Shan; Huang, Li-Chi
Previous studies separately examined the effects of positioning or environmental stressors on preterm infants' sleep and stress. Since positioning and environmental stressors occur simultaneously during infant hospitalization exploring these variables in the same study may offer new insights. A quasi-experimental study by one-group interrupted time-series design. In the current study, a total of 22 preterm infants were enrolled. Each infant was moved to either the supine or prone position for an hour at a time. Infants were videotaped and the sleep–wake states, stress behaviours and environmental conditions (light, noise and stimulation/handling) were recorded during the observation period. A total of 80 observations from 22 infants were accrued. In the supine position, preterm infants demonstrated more frequent waking states after adjusting for various environmental stressors ( p < .01). These infants demonstrated more frequent stress behaviours in the supine position after adjusting for various environmental stressors ( p < .01). These results suggest that the prone position is a more favourable position for facilitating sleep and reducing stress for preterm infants exposed to varying environmental stressors. Preterm infants present different stress behaviours in response to varying types of environmental stimuli.